O empreendedor possível na cafeicultura de Ribeirão Preto: Joaquim da Cunha Diniz Junqueira (1890-1915) - Monti, Carlo Guimarães [UNESP] (2014)
This work analyzes the many economic activities that Joaquim da Cunha Diniz Junqueira developed, such as a farmer, coffee grower, salesman, coffee dealer, owner of a commission house e politician, between the years of 1890 and 1915 in Ribeirão Preto/SP. The documentation used in the research was scattered in private and public files, and demanded a large treatment, in order to promote a reflection over the socioeconomic relations of the character inside the historical context. The work seeks to understand the businesses engaged by Joaquim da Cunha Diniz Junqueira, that tended to approach of the dynamic logic that was common to the period and that, at the same time, based on traditional and familiar traditions. The work demonstrates how he fomented the diversification of the economical ventures. The research also investigates the stratagems and economical practices among traditional and rational behaviors. It also explains how business was related to mortgages, loans and to a commission house. Besides, it examines the constitution, organization and production of coffee in the Boa Vista Farm, propriety that synthesizes a great part of the economic behavior of the historical agent here studied